“Keeping Pandora's (ballot) box half-shut”: a comparative inquiry into the institutional limits of external voting in EU Member States - Arrighi de Casanova, Jean-Thomas; Hutcheson, Derek (My University, 2015)
The article compares the institutional constraints that limit the potential electoral impact of external voting in national legislative elections in the 28 Member States of the European Union (EU). It shows that the discrepancy between policy aims and outcomes can be mainly attributed to a variety of institutional constraints restricting the scope of the policy (through residence and professional qualifications); limiting eligible voters’ access to the ballot (through cumbersome registration procedures and voting methods); and reducing the electoral weight attributed to their votes (through distinct modes of representation). It argues that the discrepancy is at least partly the result of a combination of electoral and normative concerns about the influence that external voters could and should have in elections. Institutional restrictions on the franchise of external citizens may be interpreted as a way to keep the “Pandora's box” of unexpected electoral consequences half-shut, by extending the suffrage to a traditionally excluded electorate while at the same time moderating the implications.
Keywords: external voting; EU; swamping; tipping; access to the ballot